Os requisitos do erro de acordo com a teoria adotada pelo código civil brasileiro de 2002 - Bufulin, Augusto Passamani (2013)
What is sought in this study is what are the requirements for the error that it sullied by legal business might be invalidated. The concern with the study of matter arises from the fact that both the doctrine, as the case law, have not yet found satisfactory results matching to look into the problem. We understand that for a better understanding of matter, the approach must necessarily begin in the spotlight of the theory of legal business. Thus, we studied the various interpretive theories exist about the legal business, safeguarding our point of view in the sense that the adoption of a single theory does not solve all the problems brought by the divergence between the will and the declaration. We believe it is necessary to focus specifically on the institute who want to discover and law system adopted by the country under study. So, after studying the theories of the transaction, we give our opinions on the theory adopted by the Civil Code of 2002 in relation to the error in the legal business. After, crossing error in the study of comparative law, with particular attention to the legal prepared contemporaneously with the Brazilian Civil Code, we discuss the concept, existing classifications and distinguish the normative figure of error for the other vices of legal business, with which he guard similarities but that should not be confused whit it. Then we entered the requirements analysis of the error imposed by the Civil Code of 2002, separating the various hypotheses of substantial error, the error indifferent to the invalidation of the transaction. It approaches many points still unclear on the matter, as the false reason, the calculation error, the error current and future error, the difference between error, covert defect and contract review, until we reach the second requirement that the law requires that the legal transaction may be invalidated. At this point, we paid special attention to the design of the 2002 Civil Code and all particulars on this theme, as the situations that derogations to knowability error by receptor that occur in the field of wills, contracts and free in marriage. We debated whether excusability the error is still a requirement imposed by law or was abandoned by the Civil Code of 2002. We began the study of comparative law in the face, then passed the analysis of the position taken during the Civil Code of 1916, until we reach the present moment, after the enactment of the 2002 Civil Code, giving our position on the subject. We try to answer the question concerning the possibility of payment of damages generated by the invalidation of the business, due to both the declarant to receptor as the opposite case, we called for indemnity reverse, which is the possibility of payment of damages by receptor the declarant. We study also the temporal effects of the cancellation of the deal, with the projection of its effects only for the future, and also for the last point for which we employ the undeniable contribution of various foreign codes and finally we seek to know what is the beginning of the statutory limitation period for filing the lawsuit seeking to invalidate the deal tainted by error. We chose to leave our conclusions printed in the course of all the work, so that at the end of each topic discussed, summarize positions adopted by us, subject of a separate chapter to the final conclusions, which seemed necessary and useful to better analysis of the subject